The influence of polymer latex and silica fume additives on the properties of cement mortar and concrete - Vektaris, Bronius; Smetonaitė, Edita; Vilkas, Vytis (Journal of Civil Engineering and Management, 2003)
The article maintains that while mixing acryliated latex, cement, fillings, and relaxing additives, flexible, resilient and well sticking to concrete mortars are obtained. Their properties – the lengthening of a mortar layer, tensile strength and strength of adhesion to concrete – may be regulated while changing the quantities of cement and plasticisers. 10–30% silica fume and Stoniškiai carbonate opoca additives grant to usual Portland cement mortar or concrete the resistance to sulfate corrosion. When the quantity of cement in concrete exceeds 400 kg/m3, an increased quantity of hydraulic additive is necessary 20–30%. Opoca additive ensures a better Portland cement resistance to sulfate action than the same quantity of CaCO3 and Norwegian silica fume mixture. This fact is explained by a larger activity of opoca. However silica fume activity may be increased by reducing silica fume to smaller units, for example by mixing it with coarse aggregate. In hardening, concrete silica fume and other hydraulic additives react with Ca(OH)2 deriving from cement, that's why in hardened concrete free lime diminishes and less secondary expansion units are created. There are vivid peaks of CaSO4 · 2H2O and Ca(OH)2 in XRD patterns of decayed samples. This research shows that gypsum formation is the main reason of concrete decay in Na2SO4 solution.First Published Online: 26 Jul 2012